A CRM adoption model for Malaysian telecommunication and financial companies - Chavoshi, Maryam (2013)
In recent years, the use of technology has grown increasingly to improve and assist organizations in managing their function and process. Being one of the most famous business management applications, Customer Relationship Management (CRM) plays an important role in creating beneficial and long-term relationships among customers and stockholders. A good technology is beneficial to a company, only if it has been adopted correctly. In case of CRM, it is important to understand the potential customers beside the process and factors influencing their decision for adopting CRM. This research examines and focuses on the adoption of CRM which has a significant contribution in the marketing domain. One of the most important issues for marketers is to find factors affecting the intention of organizations for the CRM adoption. Environmental factors, organizational factors, and technology characteristics are considered as three main factors affecting the intention of companies to adopt CRM system at organizational level. These factors are examined in the form of a single level model which only includes the organizational level. Multiple regression method is used for calculation and analysis of correlations between the three main factors of the research model considered as independent variable and intention of organizations for the CRM adoption considered as dependent variable. The influence of each factor is discussed with further research opportunities highlighted.